Impact of Home Care Admission Nurses' Goals on Electronic Health Record Documentation Strategies at the Point of Care - Yang, Yushi; Bass, Ellen J; Bowles, Kathryn H; Sockolow, Paulina S (Computers, informatics, nursing, 2019)
Home care nurses have multiple goals at the patient admission visit. Electronic health records support some of these goals, including high-quality documentation, but nurses may not complete the electronic documentation at the point of care. To characterize admission nurses' practices at the point of care and lay the foundation for design recommendations, this study investigates admission nurses' documentation strategies with respect to entering electronic data and how nursing goals affect them. We conducted 10 observations of home care agency admissions with five admission nurses in rural Pennsylvania. We collected screenshots and recorded the admission process. We asked the nurses questions outside the point of care. We coded the nurses' strategies at the data-entry screen level. Using thematic analysis, we investigated the influence of nursing goals on documentation strategies. Subject matter experts reviewed our findings. Several goals affect nurses' documentation strategies: ensure data accuracy, reduce time in the patient's home, and prevent infection. Home care admission nurses distribute the electronic documentation temporally due to their goals. Nurses developed memory aids to support completion of the documentation after leaving the patients' homes. Design and training should support the distributed manner in which home care nurses document patient encounters.